Anoxic-aerobic microbial fuel cell in treating spent caustic wastewater: varies in electrode pairs - Norsafiah, Fazli; Noor Sabrina, Ahmad Mutamim; Tengku Indok Munirah, Daeng Yacob (Universiti Malaysia Pahang, 2018)
In this study, the performance of a continuous fed anoxic-aerobic Microbial Fuel Cell (MFC) reactor operated with spent caustic wastewater was investigated by varying the electrode pairs of different cathode materials. Three types of electrode pairs tested were carbon-carbon (C-C), carbon-aluminium (C-Al) and carbon-copper (C-Cu). Spent caustic wastewater is the industrial wastewater with high COD concentration influenced by its high sulfur content, high salinity and high alkalinity. Little is known on the capacity of MFC to treat spent caustic wastewater, therefore the present study employed spent caustic wastewater as the feed wastewater. The performance of MFC with different electrode pairs was evaluated in terms of the voltage production, Chemical Oxygen Demand (COD) and sulfide removal efficiency. From the study, C-C electrode pairs was the best electrode pairs for the MFC operation with the highest voltage production of 189.1 mV and highest COD and sulfide removal effiaciency of 89.1% and 99.91% respectively.